AWARENESS AND PRACTICE REGARDING CERVICAL CANCER PREVENTION AMONG FEMALE COLLEGE STUDENTS OF MANGALORE CITY, INDIA - Kulkarni, Vaman; Bb, Darshan; Tandon, Abhishek; Unnikrishnan, Bhaskaran; Iyer, Sriranjani; Kukreja, Amodini; Maqbool, Amina; Bhandari, Pallav; Yadav, Jitender; Thapar, Rekha; Mithra P, Prasanna; Kumar, Nithin; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective:To determine the awareness and practice of female college students in Mangalore in relation to cervical cancer. Methods:A cross-sectional study was carried out among 270 female students from various pre-university and degree colleges in Mangalore. A semi-structured, self-administered questionnaire was used to collect data. Convenient sampling was done. Data was entered and analyzed using SPSS v. 11. Ethical approval was obtained from the Institutional Ethics Committee of Kasturba Medical College, Mangalore. Results: Very few of the participants 43 (16.5%) were aware that cervical cancer is the most common gynecological cancers in India. Awareness levels regarding various risk factors were as follows: poor genital hygiene (n=154, 59.2%), multiple sex partners (n=85, 32.7%), multiple pregnancies (n=54, 20.8%) and early initiation of sexual activities (n=52, 20.0%). Regarding the preventive measures of cervical cancer, 21 (8.1%) of the study participants had heard about the Pap test whereas none of the participants had undergone the test. Forty five (17.3%) of the students mentioned that they were aware of the presence of a vaccine. Conclusion:Majority of our study group were unaware of the various risk factors of cervical cancer and its preventable nature. Awareness regarding the association between diets, multiple pregnancies was also poor. Awareness generationthrough campaigns and other modes are the need of hour to check the rapidly increasing incidence of cervix cancer. Key words: Cross-Sectional Studies; Female; Risk Factors; Cervical cancer